2016
DOI: 10.3389/fsurg.2016.00061
|View full text |Cite
|
Sign up to set email alerts
|

Genetics Underlying an Individualized Approach to Adult Spinal Disorders

Abstract: Adult spinal disorders are a significant cause of morbidity across the world and carry significant health and economic burdens. Genetic predispositions are increasingly considered for these conditions and are becoming understood. Advances in molecular technologies since the mid-1990s have made possible genetic characterizations of these diseases in many populations, and recent findings have provided insight into the underlying pathophysiologic mechanisms. These studies have made clear the genetic heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
2
0
1
Order By: Relevance
“…Internal and external factors that lead to the disruption of IVD homeostasis include: (1) genetic factors. Genetic diversity studies can explain the susceptibility of certain populations to IDD [18,19]. Recent studies have found that long noncoding RNA can accelerate IDD by affecting the apoptosis of IVD cells and the synthesis of related proteins.…”
Section: Degeneration and Microenvironment Changesmentioning
confidence: 99%
“…Internal and external factors that lead to the disruption of IVD homeostasis include: (1) genetic factors. Genetic diversity studies can explain the susceptibility of certain populations to IDD [18,19]. Recent studies have found that long noncoding RNA can accelerate IDD by affecting the apoptosis of IVD cells and the synthesis of related proteins.…”
Section: Degeneration and Microenvironment Changesmentioning
confidence: 99%
“…Spinal disorders involve structural changes in the components of the spine, including the bones, intervertebral discs, muscles, and ligaments, which may stimulate the spinal cord and spinal nerves ( 1 ). Neurological disorders encompass a wide range of conditions, including cerebrovascular diseases, neuroimmune disorders, central nervous system infections, peripheral nerve diseases, and spinal cord diseases ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estes genes regulam a fisiologia do disco intervertebral, agindo sobre a estrutura, a homeostase e a regeneração, determinando assim os mecanismos de manutenção da estrutura discal. 11 O conhecimento destes genes poderá ajudar a definir os pacientes mais suscetíveis à DD, permitir intervenções mais precoces e, mais importante, ajudar no desenvolvimento de terapêuticas mais efetivas.…”
Section: Introductionunclassified